2019
DOI: 10.1038/s41598-019-38808-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol emission and superemission during human speech increase with voice loudness

Abstract: Mechanistic hypotheses about airborne infectious disease transmission have traditionally emphasized the role of coughing and sneezing, which are dramatic expiratory events that yield both easily visible droplets and large quantities of particles too small to see by eye. Nonetheless, it has long been known that normal speech also yields large quantities of particles that are too small to see by eye, but are large enough to carry a variety of communicable respiratory pathogens. Here we show that the rate of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
1,068
6
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 866 publications
(1,193 citation statements)
references
References 53 publications
66
1,068
6
27
Order By: Relevance
“…Choir practice attendees had multiple opportunities for droplet transmission from close contact or fomite transmission (9), and the act of singing itself might have contributed to SARS-CoV-2 transmission. Aerosol emission during speech has been correlated with loudness of vocalization, and certain persons, who release an order of magnitude more particles than their peers, have been referred to as superemitters and have been hypothesized to contribute to superspeading events (1). Members had an intense and prolonged exposure, singing while sitting 6-10 inches from one another, possibly emitting aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…Choir practice attendees had multiple opportunities for droplet transmission from close contact or fomite transmission (9), and the act of singing itself might have contributed to SARS-CoV-2 transmission. Aerosol emission during speech has been correlated with loudness of vocalization, and certain persons, who release an order of magnitude more particles than their peers, have been referred to as superemitters and have been hypothesized to contribute to superspeading events (1). Members had an intense and prolonged exposure, singing while sitting 6-10 inches from one another, possibly emitting aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…Ordinary speech aerosolizes significant quantities of respiratory particles. Experimental work by Morawska et al (2009) indicated that vocalization emits up to an order of magnitude more aerosol particles than breathing, and recent work by Asadi et al (2019) established that the louder one speaks, the more aerosol particles are produced. Asadi et al further established that, for unclear reasons, certain individuals are "speech superemitters" who emit an order of magnitude more aerosol particles than average, about 10 particles/second.…”
Section: Editorialmentioning
confidence: 99%
“…Beyond coughing and sneezing, normal speech and breathing can also generate aerosol. The size of aerosol generated by speaking and breathing is similar, ranging from 0.75 to 1.1 μm, but is notably smaller than those generated by coughing or sneezing, i.e.,~5 μm [25]. Prior studies that collected exhaled breath condensate from influenza patients have demonstrated that this respiratory virus could be emitted just by breathing [26].…”
Section: Routes Of Aerosol Generationmentioning
confidence: 99%
“…The concentration of aerosol released by the combination of speaking and breathing for more than 4 min is equivalent to the amount of aerosol emitted for 30 s of singing or coughing [15,27,28]. The volume of speech can further influence aerosol release, leading to variations in emission rates between individuals that may impact their capacity for viral transmission [25]; this is relevant, in particular, for infected individuals that are pre-symptomatic or have asymptomatic illness. Transmission of aerosol generated through these routes over short distances has been supported by recent case studies of family clusters in various Chinese cities [29,30], a restaurant setting in Guangzhou, China, [31] and a choir group in Mount Vernon, WA, USA [32].…”
Section: Routes Of Aerosol Generationmentioning
confidence: 99%